All Impostors Aren’t Alike – Differentiating the Impostor Phenomenon - Leonhardt, Mona; Bechtoldt, Myriam N.; Rohrmann, Sonja (Frontiers in Psychology, 2017)
Following up on earlier investigations, the present paper analyzes construct validity of the impostor phenomenon. It examines the question whether the impostor phenomenon is a homogeneous construct or whether different types of persons with impostor self-concept can be distinguished on the basis of related characteristics. The study was conducted with professionals in leadership positions exhibiting a pronounced impostor self-concept (N = 183). Cluster-analytic procedures indicated the existence of two different types: one group which, in line with the literature (e.g., Clance, 1985), possessed traits classified as fairly unfavorable ("true impostors") and another group which can be described as largely unencumbered ("strategic impostors"). The present study suggests two types of impostorism: “True” impostors characterized by the negative self-views associated with the construct definition, and more “strategic” impostors who seem to be less encumbered by self-doubt. It is assumed that "strategic impostors" are characterized by a form of deliberate self-presentation. Therefore, the impostor self-concept cannot principally be viewed as a dysfunctional personality style. This distinction should be more carefully considered in further research and in therapeutic interventions.